Aplikasi Pengenalan Huruf dan Angka Menggunakan Pendekatan Realistik Berbasis Android - Wanti Rahayu; Ari Irawan (SAP (Susunan Artikel Pendidikan), 2021)
This research intends to create a letter and number recognition application for kindergarten with a realistic approach using Android. The outbreak of the Covid 19 pandemic has resulted online learning from the level of kindergarten to college students. The research method used was RnD (Research and Development) using ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. This research has come to the stage of limited trial. The result of this research was the analysis stage, in which the researcher conducted a needs analysis at the research location, kindergartens in Jakarta. The design stage where the researcher created a design of the application and what buttons were needed in the screen display. The development stage where the researcher created an application that was ready to be tested in a simple and limited way to be able to see the inputs, advantages and disadvantages in the application. The next stage was an evaluation by creating improvements based on apkar input and the results of limited trials carried out at the implementation stage